Analisa Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai PDAM Xyz: Analysis of the Effect of Work Discipline on the Performance of PDAM Xyz Employees - Marwan, Marwan; Ismail, Ismail (YCMM, 2021)
PDAM XYZ is one of the Regional Owned Enterprises that is engaged in drinking water services, this of course consumers need employees who have the ability to communicate, honesty, cooperation, be alert in doing their jobs and accompanied by a work discipline attitude so that their performance becomes optimal. The company experienced several employee problems, namely employee discipline and performance. The purpose of this study is to analyze the effect of work discipline on employee performance. The methodology used in this study is a qualitative method, namely by comparing facts and theories. the results of the research conducted, the direction of the regression coefficient of the work discipline variable affecting employee performance is 0.616 with a positive direction assuming other variables are constant. It can be concluded that the significance level of 5% work discipline has a positive and significant effect on employee performance, and based on the results of hypothesis testing regarding performance employees, the results obtained that work discipline has a significant effect on employee performance at PDAM XYZ.